Агония „красного человека”: сложные дилеммы Светланы Алексиевич - Poliszczuk, Jarosław (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article is dedicated to the Svetlana Alexievich literary works in the cultural and social context of our time. As the writer has recognized, she writes about the end of the epoch which was called homo sovieticus. She paid a great attention to the traumatic experience regardless of to whom it belongs: to the Soviet servants or theirs victims – the ones who were repressed and called dissidents. Humanistic pathos is one of the main features of Svetlana Alexievich’s writings. It overestimates the value of individuality and private life in the contemporary society.